Knowledge, attitude and practices regarding malaria among residents of rural Mangalore, India - Gupta, Animesh; Bhat, Aishwarya (International Journal of Research in Medical Sciences, 2018)
Background: Malaria is one of the most prevalent parasitic diseases worldwide and India has fourth highest number of malaria cases and deaths in the world. Prevention of the disease through better knowledge and awareness is the appropriate way to keep the disease away and remain healthy. Thus, the present study was aimed to assess the knowledge, attitude and practices regarding malaria among residents of Mangalore. Methods: Community based cross sectional study was conducted among residents in Mangalore. The data was collected by using pre-tested semi-structured questionnaire which include socio-demographic data, basic knowledge about malaria, transmission and preventive measures and health seeking behaviour regarding malaria through interview method. Results: Almost 98.4% respondents heard of malaria disease and 96% respondents had knowledge that malaria is caused by mosquito bite. Even, majority (72%) of respondents knew that malaria can be fatal. Regarding the symptoms of malaria, 52.4% respondents mentioned fever with chills and 11.6% respondents don’t know about malarial symptoms. Conclusions: Majority of the respondents were familiar with the malaria symptoms, mode of transmission and vector control measures. They had good knowledge of malaria disease and good practices of malaria control measures.